Pengaruh Waktu Ekstraksi dan Konsentrasi Ekstrak Rambut Jagung (Corn Silk) Terhadap pH, Total Fenol Dan Aktivitas Antibakteri - Haslina, Haslina; Untari, Sri (Universitas Semarang, 2017)
The growth of microorganisms in foodstuffs can lead to profitable changes such as nutritional improvements in food, digestibility or storage. In addition, the growth of microorganisms in food can also lead to undesirable physical and chemical changes, so the food is not worth consuming. Staphylococcus aureus and Escherichia coli are the bacteria that often cause infection in humans. To prevent this it is necessary to have bioactive components that can inhibit the growth of microorganisms. Active compounds such as saponins, triterpenoids, phenols, tannins, flavonoids and alkaloids are known to have antibacterial activity. Several studies have reported the chemical content found in corn hair. Corn hair is part of a corn plant that has not been used effectively because it is considered as waste. Based on research, corn hair contains proteins, vitamins, carbohydrates, calcium salts, potassium, magnesium, and sodium, essential oils, steroids such as sitosterol and stigmasterol, alkaloids, saponins, tannins, and flavonoids. So presumably corn hair extract has antibacterial activity.This study aims to determine the effect of extraction time and concentration of corn hair extract on pH, total phenol and antibacterial activity.The experimental design used in this study was Randomized Block Design (RBD) with 3 replications. The treatments used were Extraction Time A1 = 30 minutes, A2 = 40 minutes, A3 = 50 minutes and Concentration Extract (material: solvent) K1 = 75% (w / v), K2 = 50% (w / v), K3 = 25% (w / v). Furthermore, the data obtained were analyzed variant and if there was any difference between treatments followed by Duncan Multiple Range Test (DMRT) test at 5% level. The results showed that all treatments produced bioactive compounds and formed inhibit zone of each test bacteria. The best time to obtain an antibacterial antibacterial extract on corn hair is 50 minutes. This was supported by the lowest pH average of 5.1 and the highest mean total phenol obtained from treatment A3 (50 minutes) was 7288,64 Î¼gGAE / g and at 75% concentration formed the largest bacterial inhibition zone in each test bacteria.